2009
DOI: 10.1016/j.icarus.2009.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Extreme sensitivity of the YORP effect to small-scale topography

Abstract: Radiation recoil (YORP) torques are shown to be extremely sensitive to small-scale surface topography, using numerical simulations. Starting from a set of "base objects" representative of the near-Earth object population, random realizations of three types of small-scale topography are added: Gaussian surface fluctuations, craters, and boulders. For each, the expected relative errors in the spin and obliquity components of the YORP torque caused by the observationally unresolved small-scale topography are comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
174
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(179 citation statements)
references
References 48 publications
4
174
0
1
Order By: Relevance
“…As pointed out in [Statler 2009], small changes in the surface of the body, and so in the illumination model, yield significant effects on the rotation. A better analytical model for the illumination of the body, including selfshadowing and finite thermal inertia, is necessary to describe the rotational dynamics under the YORP torque in a more accurate way.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As pointed out in [Statler 2009], small changes in the surface of the body, and so in the illumination model, yield significant effects on the rotation. A better analytical model for the illumination of the body, including selfshadowing and finite thermal inertia, is necessary to describe the rotational dynamics under the YORP torque in a more accurate way.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that these differences are due to the fact that they also included gravitational torques due to the Sun and to the different model they used for the illumination function, which is more realistic in the numerical simulations and it can easily destroy the integrability of our simplified model. It is worth to notice that in [Statler 2009] it is shown, using full numerical simulations, the sensitivity of the YORP effect to small changes in the shape of the body.…”
Section: The Illumination Functionmentioning
confidence: 99%
“…Especially when previous studies have shown that the YORP effect can be highly sensitive to unresolved shape features and surface roughness (Statler 2009;Rozitis & Green 2012), the shape model resolution (Breiter et al 2009), and internal bulk density distribution (Scheeres & Gaskell 2008;Lowry et al 2014). However, Geographos has a relatively high YORPcoefficient of 0.01 (see Rossi et al 2009or Rozitis & Green 2013b for a definition), and Rozitis & Green (2013a) showed that asteroids with high values are less sensitive to the inclusion of concavities in their global shape model.…”
Section: Modelling Critiquesmentioning
confidence: 99%
“…All known recipes for computing the YORP torques can be roughly divided in two main groups: most of them use a discrete mesh, summing the contributions from each triangular face (Vokrouhlický &Čapek 2002;Čapek & Vokrouhlický 2004;Scheeres 2007;Statler 2009), whereas others use a continuous shape model described in terms of spherical harmonics (Breiter & Michalska 2008;Mysen 2008;Nesvorný & Vokrouhlický 2008). The latter group cannot be applied to Itokawa, because its irregular shape, not being starlike, cannot be expressed in terms of spherical harmonics.…”
Section: Computational Modelmentioning
confidence: 99%